PENERAPAN AKUNTANSI KOPERASI PADA KOPERASI SIMPAN PINJAM (KSP) MUTIARA DI DESA LATERI: (Implementasi Peraturan Menteri Koperasi Dan UKM Nomor 2 Tahun 2024) - Silvania M. Salamony; Daniel Yohannis Titapasanea; Junus Paulus Patty (P3M Politeknik Negeri Ambon, 2024)
This research aims to understand how Cooperative Accounting is applied at the Mutiara Savings and Loan Cooperative (KSP) in Lateri Village within the framework of the implementation of the Minister of Cooperative and SMEs Regulation No. 2 of 2024. To achieve this objective, documentation and interviews were used to obtain data such as columnar balances, comparative balances, operating result calculations, and other necessary information fot this study. The research found that the financial reports produced by KSP Mutiara do not yet comply with the financial reporting requirements according to Regulation No.2 of 2024. Therefore, it is hoped that KSP Mutiara will be able to prepare financial repoarts in accordance with Regulation N0.2 of 2024 in the future.